High-whiteness EVA chemical foaming sole material and preparation method thereof

By introducing 6-hydroxy-1,2,3,4-tetrahydroquinoline and nano-zinc carbonate into EVA chemical foaming material, stable colorless complexes and metal coordination complexes are formed, solving the yellowing problem of EVA foamed shoe soles, achieving high whiteness and excellent durability, and meeting the high-quality requirements of sports shoes.

CN121108623AActive Publication Date: 2025-12-12ANTA (CHINA) CO LTD

Patent Information

Application Number
CN202511677260.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-17
Publication Date
2025-12-12
Estimated Expiration
2045-11-17

AI Technical Summary

Technical Problem

Existing EVA chemical foam shoe sole materials are prone to yellowing during the foaming process, and existing solutions have problems such as the release of toxic gases, reduced light transmittance, or poor long-term performance.

Method used

Using EVA composite raw materials, including 6-hydroxy-1,2,3,4-tetrahydroquinoline and nano zinc carbonate, the oxidation pathway of biuret is blocked by forming stable colorless complexes and metal coordination complexes, and the oxidation reaction is interrupted by acting as a free radical scavenger, thus eliminating the yellowing effect of biuret.

Benefits of technology

It achieves high whiteness (≥80%) in EVA foam soles, improving aesthetics and durability without affecting the sole's elasticity, pressure resistance, and comfort, meeting the high-quality requirements of athletic shoes, and the effect is permanent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121108623A_ABST
    Figure CN121108623A_ABST
Patent Text Reader

Abstract

The invention discloses a high-whiteness EVA chemical foaming sole material and a preparation method thereof, and belongs to the technical field of footwear products. The EVA chemical foaming sole material is formed by chemical foaming of an EVA composite raw material. The EVA composite raw materials mainly comprise 50 to 70 parts of EVA, 20 to 40 parts of an olefin thermoplastic elastomer, 0.4 to 0.7 part of a peroxide cross-linking agent, 2 to 4 parts of an AC foaming agent, 1 to 2 parts of zinc oxide, 0.3 to 0.8 part of 6-hydroxy-1, 2, 3, 4-tetrahydroquinoline, 0.5 to 1 part of nano zinc carbonate and 0.5 to 1 part of pentaerythritol tetrastearate. The whitening effect of the sole material can be realized on the premise of protecting the EVA foaming-crosslinking structure; therefore, the attractiveness of the product is improved, the durability is better, the mechanical properties and other properties of the EVA foamed sole are not influenced, and the high-quality requirements of elasticity, pressure resistance, comfort and the like of sports shoes can be met.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of footwear products, in particular to a high-whiteness EVA chemical foaming shoe sole material and a preparation method thereof. BACKGROUND

[0002] Ethylene-vinyl acetate copolymer (EVA) foaming material is widely used in shoe materials, packaging and sports equipment due to its excellent resilience, cushioning performance and processing performance. Currently, the foaming agents mainly used in EVA chemical foaming shoe soles include azodicarbonamide (AC foaming agent), 4,4'-oxobisbenzenesulfonyl hydrazide (foaming agent OBSH), white foaming agent sodium bicarbonate, foaming agent H (diazisopentamethylene tetramine), etc. Among them, AC foaming agent is the most commonly used in terms of gas generation amount, gas generation efficiency and foaming results; however, it may cause the EVA foaming shoe sole to present a yellow color to some extent.

[0003] This is because AC foaming agent decomposes at a heating condition of 170-200℃, first producing nitrogen (N2), carbon dioxide (CO2) and ammonia (NH3) and other gases, which form micro-bubbles in the EVA material to achieve the foaming effect, but at the same time, solid by-product biuret is inevitably generated. Firstly, the biuret particles themselves have a weak yellow color, and these particles are dispersed and physically adsorbed on the surface and inside of the EVA material, and as the biuret content increases, the yellow color gradually deepens. Secondly, the biuret molecule contains active amino (-NH-) and carbonyl (-CO-) functional groups, which undergo condensation reaction with the vinyl acetate groups in the EVA molecule under high temperature conditions of 170-200℃ to form products with conjugated structure; these products can absorb blue-violet light and reflect yellow light, resulting in a yellow material. Thirdly, biuret microcrystals form a specific crystal structure in the EVA matrix, and the scattering and absorption properties of this crystal structure to light cause the material to present a yellow color, and the crystal size and distribution affect the degree of yellowing. Fourthly, the N-H bond in the biuret molecule is excited under ultraviolet light to form free radicals, which then react with oxygen to form conjugated structures, causing the material to absorb the blue-violet region of the visible light spectrum and present a yellow color.

[0004] Currently, the methods for solving the yellowing of EVA foaming material in the industry generally include: using non-AC foaming agents such as foaming agent H or white foaming agent sodium bicarbonate; or mainly adding fluorescent whitening agent and titanium dioxide to adjust the color. However, if foaming agent H is used, it is moderately toxic and releases harmful gases such as nitrogen oxides during decomposition; if white foaming agent sodium bicarbonate is used, only coarse / micro-porous foaming shoe soles can be prepared, because the white foaming agent is a low-temperature foaming agent, so it is foamed first and then crosslinked.

[0005] If the above color matching method is used, on the one hand, titanium dioxide will increase the specific gravity of the shoe sole, and on the other hand, the foamed shoe sole added with titanium dioxide usually has a decreased light transmittance, and cannot obtain a natural appearance, affecting the appearance. Although the EVA foamed shoe sole added with the fluorescent whitening agent looks whiter and brighter at the beginning, over time, especially when the product is exposed to sunlight for a long time, some types of fluorescent whitening agents can cause the shoe sole to gradually turn yellow or lose the original gloss. This is mainly because the fluorescent whitening agent absorbs ultraviolet light and reflects blue light to cover up the yellow tone, but this effect is not permanent, and with the aging of the material and the influence of external environmental factors, the shoe sole may eventually turn yellow. Moreover, long-term contact with the fluorescent whitening agent can have adverse effects on human health, including the possibility of causing skin allergic reactions, such as local itching, swelling and pain. SUMMARY

[0006] In view of the deficiencies of the prior art, the present application provides a high-whiteness EVA chemical foaming shoe sole material and a preparation method thereof. The EVA chemical foaming material provided by the present application has good whiteness effect, not only improves the long-term appearance of the shoe sole product, but also does not affect the performance of the EVA foamed shoe sole, meeting the quality requirements of sports shoes in terms of elasticity, pressure resistance and safety.

[0007] The present application provides a high-whiteness EVA chemical foaming shoe sole material formed by chemical foaming of an EVA composite raw material; the EVA composite raw material comprises the following components in parts by weight:

[0008] 50-70 parts of EVA, 20-40 parts of an olefin thermoplastic elastomer, 0-20 parts of a rubber elastomer, 0-20 parts of a polyamide or polyester elastomer, 0-20 parts of a styrene elastomer, 0-5 parts of a maleic anhydride grafted-EVA compatibilizer, 0.4-0.7 parts of a peroxide crosslinking agent, 2-4 parts of an AC foaming agent, 1-2 parts of zinc oxide, 0.3-0.8 parts of 6-hydroxy-1,2,3,4-tetrahydroquinoline, 0.5-1 part of nano-zinc carbonate and 0.5-1 part of pentaerythritol tetra stearate.

[0009] In some embodiments, the mass content of VA in the EVA is 15-40%; the olefin thermoplastic elastomer is an ethylene-octene polymer and / or an ethylene-propylene-non-conjugated diene polymer.

[0010] In some embodiments, the weight fraction of the rubber elastomer is 1-15 parts, and the rubber elastomer is brominated butyl rubber.

[0011] In some embodiments, the weight fraction of the polyamide or polyester elastomer is 5-15 parts, and the polyamide or polyester elastomer is one or more of a nylon elastomer, a thermoplastic polyurethane elastomer and a polyester thermoplastic elastomer.

[0012] In some embodiments, the styrene-based elastomer is 1-15 parts by weight, and the styrene-based elastomer is a styrene-ethylene / ethylene-butene-styrene block copolymer, and / or a styrene-butadiene hydrogenated polymer.

[0013] In some embodiments, the maleic anhydride-grafted EVA compatibilizer has a weight ratio of 0.1-5 parts and a grafting rate of 0.5-1%.

[0014] In some embodiments, the peroxide crosslinking agent is dicumyl peroxide and / or 1,4-di-tert-butylperoxide.

[0015] In some embodiments, the nano zinc carbonate is precipitated nano zinc carbonate with a particle size of 100~500nm.

[0016] In some embodiments, the whiteness of the EVA chemically foamed shoe sole material is ≥80%, and the density is ≤0.13g / cm³. 3 .

[0017] The present invention provides a method for preparing EVA chemically foamed shoe sole material as described above, comprising: weighing each component of EVA composite raw material according to the weight parts, and then mixing, granulating, foaming and molding to obtain EVA chemically foamed shoe sole material; wherein the foaming and molding temperatures are 170~180℃ respectively.

[0018] To obtain high-whiteness EVA foamed shoe sole material, the chemically foamed material provided by this invention is formed by chemically foaming EVA composite raw materials. By weight, the EVA composite raw materials include the following components: 50-70 parts EVA, 20-40 parts olefinic thermoplastic elastomer, 0-20 parts rubber elastomer, 0-20 parts polyamide or polyester elastomer, 0-20 parts styrene elastomer, 0-5 parts maleic anhydride grafted-EVA compatibilizer, 0.4-0.7 parts peroxide crosslinking agent, 2-4 parts AC foaming agent, 1-2 parts zinc oxide, 0.3-0.8 parts 6-hydroxy-1,2,3,4-tetrahydroquinoline, 0.5-1 parts nano zinc carbonate, and 0.5-1 parts pentaerythritol tetrastearate. This invention primarily introduces tetrahydroquinoline derivatives and nano zinc carbonate into the EVA chemical foaming formulation. First, this invention utilizes 6-hydroxy-1,2,3,4-tetrahydroquinoline in the formulation and biuret, a byproduct of the AC foaming agent, to form a stable, colorless complex. This complex blocks the oxidation pathway of biuret and acts as a free radical scavenger, interrupting the free radical chain reaction during biuret oxidation. Second, the yellowing effect of biuret is eliminated by utilizing the metal coordination complexation mechanism between nano-zinc carbonate and biuret in the formulation. This invention can achieve a whitening effect on shoe sole materials, such as whiteness ≥80%, while protecting the EVA foam-crosslinked structure. This not only improves the product's aesthetics and durability but also does not affect the mechanical and other properties of the EVA foam sole, meeting the high-quality requirements of sports shoes for elasticity, pressure resistance, and comfort. Attached Figure Description

[0019] Figure 1 This is a schematic diagram illustrating the process steps for preparing and implementing EVA chemical foaming shoe soles according to some embodiments of the present invention. Detailed Implementation

[0020] The technical solutions in the embodiments of this application are described clearly and completely below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0021] This invention provides a high-whiteness EVA chemically foamed shoe sole material, formed by chemically foaming EVA composite raw materials. By weight, the EVA composite raw materials comprise the following components: 50-70 parts EVA, 20-40 parts olefinic thermoplastic elastomer, 0-20 parts rubber elastomer, 0-20 parts polyamide or polyester elastomer, 0-20 parts styrene elastomer, 0-5 parts maleic anhydride grafted-EVA compatibilizer, 0.4-0.7 parts peroxide crosslinking agent, 2-4 parts AC foaming agent, 1-2 parts zinc oxide, 0.3-0.8 parts 6-hydroxy-1,2,3,4-tetrahydroquinoline, 0.5-1 parts nano-zinc carbonate, and 0.5-1 parts pentaerythritol tetrastearate.

[0022] The EVA chemical foaming material provided by this invention has a good whiteness effect, which not only improves the long-term aesthetics of shoe sole products, but also does not affect the various performance characteristics of EVA foam shoe soles, meeting the quality requirements of sports shoes such as elasticity, pressure resistance, and safety.

[0023] This invention is achieved through the following technical solution: the EVA composite raw material mainly comprises 50-70 parts by weight of EVA and 20-40 parts by weight of olefinic thermoplastic elastomer. EVA is the abbreviation for ethylene-vinyl acetate copolymer, which has good flexibility and chemical stability. The mass content of vinyl acetate (VA) structural units has a certain influence on the material properties. In some embodiments, the mass parts of EVA can be 50, 55, 60, or 70 parts, etc., wherein the mass content of VA can be 15%~40%. Preferred commercially available varieties include EVA UE632 (Taiwan Polymer Chemicals Co., Ltd.), with a VA mass content of 22%.

[0024] The olefin-based thermoplastic elastomers described in this invention primarily consist of thermoplastic polyolefin structures and amorphous elastomer structural units, exhibiting excellent processing and comprehensive properties. The olefin-based thermoplastic elastomers can be ethylene-octene polymers and / or ethylene-propylene-nonconjugated diene polymers, including 1-3 types of ethylene-octene random polymers (POE), ethylene-octene block polymers (OBC), and ethylene-propylene-nonconjugated diene polymers (EPDM), with a hardness of 60-63A. Preferred commercially available varieties include POE 8180 (Dow Chemical, hardness 63A), OBC 9107 (DuPont, hardness 60A), and EPDM3745P (Dow Chemical). In some preferred embodiments, POE and OBC are used in combination, with a total mass fraction of 20, 25, or 30 parts, etc.

[0025] By weight, the EVA composite material formulation includes: 0-20 parts of rubber elastomer, 0-20 parts of polyamide or polyester elastomer, and 0-20 parts of styrene elastomer. Generally, at least one of the above components has a weight percentage that is not zero, which helps to provide better elasticity, compression set, comfort, etc.

[0026] In some embodiments, the rubber elastomer may be 1-15 parts by weight; the rubber elastomer is preferably brominated butyl rubber, specifically commercially available varieties such as BIIR X2 (Lanxess AG, Germany, bromine content 1.8%). In some embodiments, the polyamide or polyester elastomer may be 5-15 parts by weight; the polyamide or polyester elastomer is one or more of nylon elastomer, thermoplastic polyurethane elastomer, and polyester thermoplastic elastomer, and the melt index of such elastomer components may be 5.6-10 g / 10 min (routine test). The polyamide or polyester elastomer includes: nylon elastomer (PEBAX), thermoplastic polyurethane elastomer (TPU), and polyester thermoplastic elastomer (TPEE), preferably commercially available varieties such as PEBAX KHX 7040 (Xinyuan Chemical Co., Ltd.), TPU EZ32-5-A (Lubrizol AG), and TPEE 4058 (Lubrizol AG).

[0027] In other embodiments, the styrene-based elastomer is 1-15 parts by weight, and the styrene-based elastomer is a styrene-ethylene / ethylene-butene-styrene block copolymer, and / or a styrene-butene hydrogenated polymer. Specifically, the styrene-based elastomer includes one of the following: styrene-ethylene-butene-styrene block copolymer (SEBS), styrene-ethylene-butene-styrene block copolymer (SBBS), and high vinyl content styrene elastomer (SOE). Preferred commercially available varieties include SEBS YH535 (Baling Petrochemical Co., Ltd.), SBBS P1083 (Asahi Kasei Corporation, Japan), and SOE L609 (Asahi Kasei Corporation, Japan, with a glass transition temperature above room temperature).

[0028] Furthermore, embodiments of the present invention preferably include a maleic anhydride-grafted EVA compatibilizer, which is 0.1-5 parts by weight; some embodiments may omit this compatibilizer. Preferably, the maleic anhydride-grafted EVA compatibilizer comprises maleic anhydride-grafted EVA with a grafting rate of 0.5-1.0%, specifically commercially available varieties such as C250 (DuPont).

[0029] In embodiments of the present invention, the EVA composite raw material comprises: 0.3-0.8 parts by weight of 6-hydroxy-1,2,3,4-tetrahydroquinoline, 0.5-1 parts by weight of nano-zinc carbonate, and 0.5-1 parts by weight of pentaerythritol tetrastearate. The 6-hydroxy-1,2,3,4-tetrahydroquinoline is a hydroxyl-substituted quinoline derivative, which is safe and environmentally friendly. The hydroxyl group (-OH) on the tetrahydroquinoline forms multiple hydrogen bonds with the carbonyl oxygen (-C=O) of biuret. The hydroxyl group and the heterocyclic nitrogen atom act as bidentate coordination sites, forming a colorless five-membered chelate ring with the biuret molecule. After the chelate complex is formed, the ring structure of the tetrahydroquinoline provides a steric shield to the active site of biuret, preventing oxygen molecules from approaching. Furthermore, it acts as a free radical scavenger, interrupting the free radical chain reaction during the oxidation of biuret.

[0030] The nano-zinc carbonate is preferably precipitated nano-zinc carbonate with a particle size of 100-500 nm, and more specifically, commercially available varieties such as YM-ZnCO3-200N are preferred. In the embodiments of the present invention, the zinc ions in the nano-zinc carbonate can form a stable coordination complex with the byproduct biuret, forming a metal-synergistic complex system and blocking the biuret oxidation pathway.

[0031] The aforementioned pentaerythritol tetrastearate has excellent nucleation properties for partially crystalline polymers, exhibits good thermal stability and low volatility at high temperatures, and has good demolding and flow properties. It can be used as a highly efficient lubricant and a synergist for chelating decolorization reactions, and can significantly improve the transparency and surface finish of products.

[0032] Meanwhile, the EVA composite raw material includes: 0.4-0.7 parts by weight of peroxide crosslinking agent, 2-4 parts by weight of AC foaming agent, and 1-2 parts by weight of zinc oxide (ZnO). The peroxide crosslinking agent includes either dicumyl peroxide or 1,4-di-tert-butylperoxyisopropylbenzene; preferably, commercially available BIBP 14S-FL is preferred. The AC foaming agent is azodicarbonamide, preferably commercially available AC6000H. Specifically, the zinc oxide has a purity of ≥99.7%, preferably commercially available ZnO997.

[0033] The EVA foam shoe sole formulation technology of this invention can effectively eliminate the yellow phase of biuret. One of the main mechanisms is the chelation decolorization mechanism: the tetrahydroquinoline derivative forms a stable colorless complex with biuret, blocking the oxidation pathway of biuret. Specifically, the -NH- group in the biuret molecule is oxidized in the presence of high temperature and oxygen to form a free radical intermediate. The free radical intermediate further initiates an oxidation chain reaction, forming a yellow product containing N=O or N=N structures. The conjugated system of the yellow oxidation product expands, enhancing the absorption of blue-violet light, resulting in the material appearing yellow. 6-Hydroxy-1,2,3,4-Tetrahydroquinoline is a nitrogen-containing heterocyclic compound containing a partially hydrogenated quinoline ring, hydrogenated at positions 1, 2, 3, and 4, with strong coordinating groups such as hydroxyl (-OH) or amino (-NH2) introduced at positions 2 and 8. On the one hand, the chelating agent also acts as a free radical scavenger, interrupting the free radical chain reaction in the biuret oxidation process. On the other hand, the -OH or -NH2 group on 6-hydroxy-1,2,3,4-tetrahydroquinoline forms multiple hydrogen bonds with the carbonyl oxygen (-C=O) of biuret. The 2-hydroxyl group and the heterocyclic nitrogen atom of 6-hydroxy-1,2,3,4-tetrahydroquinoline act as bidentate coordination sites, forming a five-membered chelate ring with the biuret molecule. Firstly, after the chelate complex is formed, the ring structure of the tetrahydroquinoline derivative provides a steric shield to the active site of biuret, preventing oxygen molecules from approaching. Secondly, chelate coordination causes a rearrangement of the π-electron cloud in the biuret molecule, disrupting the original chromophore structure; the maximum absorption wavelength of the complex shifts from the original 350-380 nm to <320 nm, no longer absorbing blue-violet light in the visible region. Therefore, the chelation effect leads to a significant change in the electronic structure of biuret, achieving a decolorizing effect and eliminating its yellow color.

[0034] This invention also utilizes a metal coordination complexation mechanism: using nano-zinc carbonate, zinc ions can form stable coordination complexes with the byproduct biuret, creating a metal-synergistic complexation system that blocks the biuret oxidation pathway. In this invention, an EVA chemical foaming formulation using AC foaming agent employs 6-hydroxy-1,2,3,4-tetrahydroquinoline and nano-zinc carbonate to develop a yellowing elimination technology for biuret, improving the whiteness of EVA chemically foamed shoe soles. This technology has significant practical value and application prospects.

[0035] Accordingly, embodiments of the present invention provide a method for preparing EVA chemically foamed shoe sole material as described above, comprising: weighing each component of EVA composite raw material according to weight parts, and then mixing, granulating, foaming and molding to obtain EVA chemically foamed shoe sole material; wherein the foaming and molding temperatures are 170~180℃ respectively.

[0036] See Figure 1The process for preparing the EVA chemically foamed shoe sole material in this embodiment of the invention can be a midsole MD chemical foaming process, the implementation steps of which include: ① weighing materials; ② mixing; ③ granulation; ④ small foaming; ⑤ secondary molding.

[0037] According to the above formulation, the peroxide crosslinking agent and AC foaming agent are weighed as the first group; 6-hydroxy-1,2,3,4-tetrahydroquinoline, nano zinc carbonate, pentaerythritol tetrastearate, and zinc oxide are weighed as the second group; and the remaining materials are weighed as the third group.

[0038] In this embodiment of the invention, the third group of materials is first poured into the internal mixer and the machine is turned on. When the temperature rises to between 85-95°C, the second group of materials is poured in. When the temperature rises to between 95-105°C, the first group of materials is poured in. When the temperature rises to between 105-120°C, the mixed materials are poured out.

[0039] Subsequently, in this embodiment of the invention, the mixed composite material is poured into the material forming machine. The temperatures of the first, second, third, and fourth zones can be adjusted to 90°C, 95°C, 100°C, and 105°C, respectively. The screw speed is adjusted to 50-70 rpm, and the cutting speed is adjusted to 20-30 rpm.

[0040] In this embodiment of the invention, the granulated material can be poured into a flat mold for small foaming to complete the first foaming (small foaming). The preferred foaming temperature is 175±5℃ and the foaming time is 530±50 seconds.

[0041] In this embodiment of the invention, the semi-finished product after small-scale foaming is allowed to cool statically for 24 hours. Then, the cooled semi-finished product is pressed into a flat hot-press mold to complete the molding process, which is a secondary molding process. The preferred hot-pressing temperature is 175±5℃; the hot-pressing time is 430±30 seconds; the cooling water temperature is 25℃, and the cooling time is 430±20 seconds. In some embodiments, the whiteness of the EVA chemically foamed shoe sole material is ≥80%, and the density is ≤0.13g / cm³. 3 .

[0042] Compared to existing EVA chemically foamed soles, this invention introduces 6-hydroxy-1,2,3,4-tetrahydroquinoline and nano-zinc carbonate into the EVA chemical foaming formula. 6-hydroxy-1,2,3,4-tetrahydroquinoline forms a stable, colorless complex with biuret, a byproduct of the AC foaming agent. This complex blocks the oxidation pathway of biuret and acts as a free radical scavenger, interrupting the free radical chain reaction during biuret oxidation. The metal coordination complex formed by the reaction of nano-zinc carbonate and biuret eliminates the yellowing effect of biuret. Furthermore, with the synergistic effect of pentaerythritol tetrastearate, a whitening effect is achieved while protecting the EVA foaming-crosslinking structure, achieving a whiteness of ≥80%. Compared to EVA chemically foamed soles without these three materials, the whiteness is increased by more than 20%, significantly improving the product's aesthetics. This is a pioneering achievement in the industry.

[0043] This invention not only effectively achieves a whitening effect but also does not affect the original properties of the EVA foam sole, such as elasticity, compression set, comfort, and mechanical properties, thus meeting the high-quality requirements of athletic shoes. Compared to traditional methods using fluorescent whitening agents or titanium dioxide, this invention avoids potential health risks and reduced light transmittance, offering greater environmental friendliness and safety. Furthermore, the elimination of biuret through chelation decolorization and metal coordination complexation is permanent, preventing the sole from yellowing again due to material aging or sunlight exposure.

[0044] To better understand the technical content of this invention, specific embodiments are provided below to further illustrate the invention. The substances used in these embodiments are commercially available.

[0045] Example 1

[0046] ① Weighing: Based on the dosage of the formula in Table 1, weigh BIBP and foaming agent as the first group; weigh 6-hydroxy-1,2,3,4-tetrahydroquinoline, nano zinc carbonate, pentaerythritol tetrastearate, and zinc oxide as the second group; weigh the remaining materials as the third group.

[0047] ② Mixing: First, pour the third batch of material into the internal mixer and turn on the machine. When the temperature rises to between 85-95℃, pour in the second batch of material. When the temperature rises to between 95-105℃, pour in the first batch of material. When the temperature rises to between 105-120℃, pour out the mixed material.

[0048] ③ Granulation: Pour the mixed material into the granulator. Adjust the temperatures of the first, second, third, and fourth zones to 90, 95, 100, and 105℃ respectively. Adjust the screw speed to 50-70 rpm and the cutting speed to 20-30 rpm.

[0049] ④ Small foaming: Pour the prepared granules into a flat mold for small foaming to complete the first foaming. The foaming temperature is 175±5℃ and the foaming time is 530±50 seconds.

[0050] ⑤ Molding: Let the foamed semi-finished product stand and cool for 24 hours, then press the foamed semi-finished product into a flat hot press mold to complete the molding of the finished product; the hot pressing temperature is 175±5℃; the hot pressing time is 430±30 seconds; the cooling water temperature is 25℃ and the cooling time is 430±20 seconds.

[0051] Example 2-16

[0052] Following the steps of Example 1, EVA chemical foamed shoe sole materials were obtained respectively. The specific formulas are shown in Table 1 and Table 2.

[0053] Comparative Examples 1-8

[0054] Following the steps in Example 1, EVA chemical foamed shoe sole materials were obtained, and the specific formulas are shown in Table 3.

[0055] Table 1. Raw material formulations for Examples 1-8:

[0056]

[0057] Table 2. Raw material formulations for Examples 9-16:

[0058]

[0059] Table 3. Raw material formulations for Comparative Examples 1-8:

[0060]

[0061] The sources of each raw material are as follows:

[0062] EVA UE632: VA molar content is 22%, hardness is 86A, melting point is 82℃, melt index is 2.2g / 10min, tensile strength is 17MPa, elongation at break is 820%, Polymer Chemicals Co., Ltd., Taiwan, China.

[0063] POE 8180: Hardness 63A, melting point 47℃, melt index 0.5g / 10min, tensile strength 6.3MPa, elongation at break 600%, Dow Chemical Company.

[0064] OBC 9107: Hardness 60A, melting point 121℃, melt index 1.0g / 10min, tensile strength 27MPa, elongation at break 1550%, DuPont.

[0065] BIIR X2: bromine content 1.8%, Mooney viscosity 42-50 ML(1+8) / 125℃, Lanxess GmbH, Germany.

[0066] PEBAX KHX 7040: Hardness 40D, melt index 10.0g / 10min, melting point 162℃, tensile strength 25MPa, elongation at break 600%, Xinyuan Chemical Co., Ltd.

[0067] TPU EZ32-5-A: Hardness 93A, Melt Flow Index 10.0g / 10min, Melting Point 127℃, Tensile Strength 40MPa, Elongation at Break 800%, Lubrizol Corporation.

[0068] TPEE 4058: Hardness 43D, melt index 5.6g / 10min, melting point 152℃, tensile strength 60MPa, elongation at break 500%, Lubrizol Corporation.

[0069] SEBS YH535: Hardness 76A, melt flow index 2.3g / 10min, tensile strength 10.5MPa, elongation at break 523%, styrene molar content 33%, Baling Petrochemical Company.

[0070] SBBS P1083: Hardness 56A, melt index 3.0g / 10min, tensile strength 9MPa, elongation at break 700%, styrene molar content 20%, 1-2 vinyl content 4%, Asahi Kasei Corporation, Japan.

[0071] SOE L609: Hardness 87A, melt flow index 2.5g / 10min, tensile strength 26MPa, elongation at break 640%, Asahi Kasei Corporation, Japan.

[0072] C250: Grafting rate 0.8%, hardness 84A, melt index 1.5g / 10min, melting point 71℃, tensile strength 11MPa, elongation at break 660%, DuPont.

[0073] BIBP 14S-FL: White granules, AkzoNobel.

[0074] AC6000H: Yellow powder, Hangzhou Haihong Fine Chemical Co., Ltd.

[0075] ZnO 997: White powder, Shipai zinc oxide, with a relative density of 4.42~4.45.

[0076] 6-Hydroxy-1,2,3,4-Tetrahydroquinoline: Tianmen Hengchang Chemical Co., Ltd.

[0077] Pentaerythritol tetrastearate: Melting point 60-66ºC, Guangzhou Shunfan New Materials Co., Ltd.

[0078] Nano zinc carbonate YM-ZnCO3-200N: Particle size 200nm, purity 99.9%, Yumu (Ningbo) New Materials Co., Ltd.

[0079] Mechanical and other performance tests were conducted on the shoe sole materials of the above embodiments and comparative examples, and the results are as follows.

[0080] Table 4 Test data for Comparative Examples 1-8

[0081]

[0082] Table 5 Test data for Examples 1-8

[0083]

[0084] Table 6 Test data for Examples 9-16

[0085]

[0086] The test data from Examples 1-8 and Comparative Examples 1-8 show that, with the same matrix, foaming agent, crosslinking agent, and zinc oxide in both examples and comparative examples, the comparative examples did not contain 6-hydroxy-1,2,3,4-tetrahydroquinoline, nano-zinc carbonate, or pentaerythritol tetrastearate, while the examples contained 0.7 parts of 6-hydroxy-1,2,3,4-tetrahydroquinoline, 0.8 parts of nano-zinc carbonate, and 0.8 parts of pentaerythritol tetrastearate. A comparison of the final foamed material properties revealed minimal changes in density, hardness, tear strength, tensile strength, rebound, compression set, and shock absorption G-value. However, the whiteness of the foamed material in the examples was more than 20% higher than that in the comparative examples. This indicates that the addition of 6-hydroxy-1,2,3,4-tetrahydroquinoline, nano-zinc carbonate, and pentaerythritol tetrastearate helps eliminate the yellow hue of the product without affecting the foaming effect and performance. This is mainly because the -OH group on 6-hydroxy-1,2,3,4-tetrahydroquinoline forms multiple hydrogen bonds with the -C=O group of biuret. The hydroxyl group and the heterocyclic nitrogen atom act as bidentate coordination sites, forming a colorless five-membered chelate ring with the biuret molecule. After the chelate complex is formed, the ring structure of tetrahydroquinoline provides a stereoprotective barrier to the active sites of biuret, preventing oxygen molecules from approaching. On the other hand, it acts as a free radical scavenger, interrupting the free radical chain reaction during the oxidation of biuret. The metal coordination complex formed by the reaction of nano-zinc carbonate and biuret eliminates the yellowing effect of biuret. Pentaerythritol tetrastearate, as a synergist and lubricant, effectively promotes the synergistic effect of the tetrahydroquinoline derivative and nano-zinc carbonate, thereby achieving a whitening and transparency-enhancing effect with a whiteness ≥80% while protecting the EVA foaming-crosslinking structure, thus improving the product's aesthetics. This demonstrates that the present invention's technique for eliminating the yellowing of biuret through the chelation decolorization reaction of 6-hydroxy-1,2,3,4-tetrahydroquinoline with biuret and the metal coordination complexation reaction of nano-zinc carbonate with biuret is feasible.

[0087] The test data from Examples 8-13 show that, by fixing the amounts of EVA, POE, OBC, TPU, C250, BIBP, AC6000H, ZnO, nano zinc carbonate, and pentaerythritol tetrastearate, and adjusting the amount of 6-hydroxy-1,2,3,4-tetrahydroquinoline added to 0.3-0.8 parts, it was found that as the amount of tetrahydroquinoline derivative increased, the whiteness of the final foamed material gradually improved. However, after adding 0.7 / 0.8 parts, the improvement in whiteness was no longer significant. Therefore, the preferred amount of tetrahydroquinoline derivative added is 0.3-0.8 parts.

[0088] The test data from Examples 8 / 14 / 16 show that, by fixing the amounts of EVA, POE, OBC, TPU EZ32-5A, C250, BIBP, AC 6000H, ZnO, 6-hydroxy-1,2,3,4-tetrahydroquinoline, and pentaerythritol tetrastearate, and adjusting the amount of nano zinc carbonate added to 0.5 / 0.7 / 0.8 / 1.0 parts, it was found that as the amount of nano zinc carbonate increased, the whiteness of the final foamed material gradually increased to 83% / 86% / 90% / 91%, respectively. The increase became relatively slow after adding up to 0.8 parts. Therefore, the preferred amount of nano zinc carbonate added is 0.5-1.0 parts.

[0089] The test data from Examples 1-8 and Comparative Examples 1-8 show that the EVA chemical foam material prepared in the embodiments of the present invention has better yellowing resistance, reaching ≥4.5, while the yellowing resistance of the comparative examples is 3.5-4. This indicates that the yellowing elimination effect of biuret through the chelate formed by the chelation decolorization reaction of 6-hydroxy-1,2,3,4-tetrahydroquinoline and biuret, and the complex formed by the metal coordination complexation reaction of nano-zinc carbonate and biuret, is permanent and will not cause the sole to yellow due to material aging or sunlight. In summary, the embodiments of the present invention achieve a better whitening effect, improve the long-term aesthetics of the sole product, and do not affect the various properties of the EVA foam sole, meeting the high-quality requirements of sports shoes such as elasticity, pressure resistance, and comfort.

[0090] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only for the purpose of helping to understand the method and core ideas of the present invention. The above descriptions are only preferred embodiments of the present invention. It should be noted that due to the limitations of textual expression, while there are objectively infinite specific structures, those skilled in the art can make several improvements, modifications, or changes without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner. These improvements, modifications, changes, or combinations, or the direct application of the inventive concept and technical solution to other situations without modification, should all be considered within the scope of protection of the present invention.

Claims

1. A high-whiteness EVA chemically foamed shoe sole material, characterized in that, It is formed by chemical foaming of EVA composite raw material; by weight, the EVA composite raw material comprises the following components: 50-70 parts EVA, 20-40 parts olefin thermoplastic elastomer, 0-20 parts rubber elastomer, 0-20 parts polyamide or polyester elastomer, 0-20 parts styrene elastomer, 0-5 parts maleic anhydride grafted-EVA compatibilizer, 0.4-0.7 parts peroxide crosslinking agent, 2-4 parts AC foaming agent, 1-2 parts zinc oxide, 0.3-0.8 parts 6-hydroxy-1,2,3,4-tetrahydroquinoline, 0.5-1 parts nano zinc carbonate, and 0.5-1 parts pentaerythritol tetrastearate.

2. The high-whiteness EVA chemically foamed shoe sole material according to claim 1, characterized in that, The EVA contains 15-40% VA by mass; the olefin thermoplastic elastomer is an ethylene-octene polymer and / or an ethylene-propylene-non-conjugated diene polymer.

3. The high-whiteness EVA chemically foamed shoe sole material according to claim 1, characterized in that, The rubber elastomer is 1-15 parts by weight, and the rubber elastomer is brominated butyl rubber.

4. The high-whiteness EVA chemically foamed shoe sole material according to claim 1, characterized in that, The polyamide or polyester elastomer is 5-15 parts by weight, and the polyamide or polyester elastomer is one or more of nylon elastomer, thermoplastic polyurethane elastomer, and polyester thermoplastic elastomer.

5. The high-whiteness EVA chemically foamed shoe sole material according to claim 1, characterized in that, The styrene-based elastomer is 1-15 parts by weight, and the styrene-based elastomer is a styrene-ethylene / ethylene-butene-styrene block copolymer, and / or a styrene-butadiene hydrogenated polymer.

6. The high-whiteness EVA chemically foamed shoe sole material according to any one of claims 1-5, characterized in that, The maleic anhydride-grafted EVA compatibilizer has a weight ratio of 0.1-5 parts and a grafting rate of 0.5-1%.

7. The high-whiteness EVA chemically foamed shoe sole material according to any one of claims 1-5, characterized in that, The peroxide crosslinking agent is dicumyl peroxide and / or 1,4-di-tert-butylperoxide.

8. The high-whiteness EVA chemically foamed shoe sole material according to any one of claims 1-5, characterized in that, The nano zinc carbonate is precipitated nano zinc carbonate with a particle size of 100~500nm.

9. The high-whiteness EVA chemically foamed shoe sole material according to any one of claims 1-5, characterized in that, The EVA chemically foamed shoe sole material has a whiteness of ≥80% and a density of ≤0.13g / cm³. 3 .

10. A method for preparing a high-whiteness EVA chemically foamed shoe sole material, used to prepare the high-whiteness EVA chemically foamed shoe sole material as described in any one of claims 1-9, characterized in that, include: The components of the EVA composite raw material are weighed according to their weight proportions, and then mixed, granulated, foamed and molded to obtain EVA chemical foamed shoe sole material; the foaming and molding temperatures are 170~180℃ respectively.

Citation Information

Patent Citations

  • High-resilience flame-retarding antistatic foamed polyethylene material

    CN102816363A

  • Foamed rubber sole special rubber material and preparation method thereof

    CN109096626A

  • Pearlescent white high-transmittance foamed midsole material, preparation method thereof and sneakers

    CN111393736A

  • Wear-resistant anti-skid sole material and preparation method thereof

    CN117304589A

  • Super-impact absorption high-resilience foaming material, and preparation method therefor and application thereof

    WO2023015693A1

Cited By

  • Shrinkage-resistant light, soft and elastic sole foaming material and preparation method thereof

    CN121378942A

  • Foaming sole material and preparation method thereof

    CN121736402A